Literature Review: The Role of Psychological Capital among Indonesianâs Worker - Prihatsanti, Unika (Universitas Ahmad Dahlan, 2017)
AbstractPsychological capitalÂ is a positive psychological state, characterizedÂ by havingÂ self-efficacy, hope, optimism, and resiliency. The findingsÂ show that psycap plays a vitalÂ role in the emergence of positive behaviors atÂ the workplace. This study aims to conduct a literature reviewÂ on the role of psychological capital in workers fromÂ various settings in Indonesia. The literature search is done through portalgaruda.org and onesearch.id database using the keywords